2011
DOI: 10.1111/j.1365-2524.2011.01021.x
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of physician assistants in primary care systems

Abstract: Shortages of primary care doctors are occurring globally; one means of meeting this demand has been the use of physician assistants (PAs). Introduced in the United States in the late 1960s to address doctor shortages, the PA movement has grown to over 75,000 providers in 2011 and spread to Australia, Canada, Great Britain, The Netherlands, Germany, Ghana, and South Africa. A purposeful literature review was undertaken to assess the contribution of PAs to primary care systems. Contemporary studies suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 54 publications
2
59
0
Order By: Relevance
“…In Ontario, both the University of Toronto and McMaster University offer two-year, Canadian Medical Association Accredited PA Programs [2]. PAs have been shown to be well-accepted by the public, as well as safe and effective primary care providers [3][4][5]. The involvement of PAs has also been shown to improve timely access to healthcare [4].…”
Section: Addressing Challenges Of Primary Care and Chronic Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ontario, both the University of Toronto and McMaster University offer two-year, Canadian Medical Association Accredited PA Programs [2]. PAs have been shown to be well-accepted by the public, as well as safe and effective primary care providers [3][4][5]. The involvement of PAs has also been shown to improve timely access to healthcare [4].…”
Section: Addressing Challenges Of Primary Care and Chronic Illnessmentioning
confidence: 99%
“…PAs have been shown to be well-accepted by the public, as well as safe and effective primary care providers [3][4][5]. The involvement of PAs has also been shown to improve timely access to healthcare [4]. Physician Assistants are well positioned to improve not only access to care, but the quality in time spent managing and educating chronically ill patients.…”
Section: Addressing Challenges Of Primary Care and Chronic Illnessmentioning
confidence: 99%
“…The research on NP, CMN, and PA practice has demonstrated consistently safe and quality care comparable to that provided by FPs. [5][6][7][8][9][10][11][12][13][14][15][16] This has been reinforced again and again for NPs, CNMs, and PAs throughout decades of practice. However, the real issue is being able to work together for the good of patients and the health of the nation.…”
mentioning
confidence: 99%
“…186 Geographically, PAs are less likely to work in rural settings than urban settings; usually the larger the Metropolitan area, the greater the PA concentration exists. 218 However, at least 9% of PAs work in rural practices with the vast majority of PA rural practices being primary care. 218 Several pertinent characteristics enhance PAs as being a healthcare workforce solution.…”
Section: Find Someone Else: Physician Assistantsmentioning
confidence: 99%
“…218 However, at least 9% of PAs work in rural practices with the vast majority of PA rural practices being primary care. 218 Several pertinent characteristics enhance PAs as being a healthcare workforce solution. First, PAs are flexible and adaptable.…”
Section: Find Someone Else: Physician Assistantsmentioning
confidence: 99%